Condição periodontal e câncer de mama: um estudo caso-controle. Resultados parciais. - Sfreddo, Camila Silveira (2014)
Recent studies have found associations between periodontal disease and some cancers. We evaluated the association between periodontal disease and breast cancer. We conducted a case-control study involving 67 women 67 women diagnosed with breast cancer (cases) treated at the University Hospital of Santa Maria, Brazil, paired for age and smoking with 67 controls recruited from outpatient units of the same hospital during the period from April 2013 to May 2014 cancer. Interview, assessment of Body Mass Index (BMI), analysis of medical records and periodontal exam were performed. We evaluated Plaque Index (IPL), Gingival Index (GI), Probing Depth (PD), Bleeding on Probing (BOP) and Clinical Attachment Level (CAL). The loss of periodontal attachment, assessed by CAL, was the predictor variable. Logistic regression evaluated the association between insertion loss and breast cancer. CAL greater than or equal to 1.69 mm was associated with breast cancer after adjustment for age [odds ratio (OR) = 2.31; confidence interval (CI) 95% = 1.02 to 5.24]. Age was also associated with breast cancer (OR = 2.17; 95% CI = 1.06-4.43). Cases had a higher family income (P = 0.02), older at first pregnancy (P = 0.04) and breastfed for less time (P = 0.01). Therefore, there were associations between CAL, age, family income, age at first birth and duration of breastfeeding with breast cancer. Association between CAL and breast cancer adjusted for age suggests that periodontal attachment loss may be a possible indicator of risk for this cancer.